2021
DOI: 10.1021/acs.energyfuels.1c00592
|View full text |Cite
|
Sign up to set email alerts
|

Micro-particle Image Velocimetry Measurements of Pore-Scale Velocity Field during Nanoparticle-Assisted Alkaline Flooding

Abstract: We report experimental investigations on the porescale flow dynamics during two-phase flow in a micromodel using the microscale particle image velocimetry (μ-PIV) technique. The combined effect of alkali (sodium carbonate) and nanoparticles (silica) on oil recovery is investigated using interfacial tension, rheology, emulsification, contact angle, chemical flooding, and micro-PIV measurements. Dynamic interfacial tension (IFT) measurement shows that silica nanoparticles significantly reduce the interfacial ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…However, the foam has the disadvantage of de-foaming in contact with oil, so the EOR is poor. , A polymer is used to increase the viscosity of the injected fluid and reduce the mobility ratio of injected fluid to crude oil to increase the swept area . But a long polymer chain would be severely fractured under the shearing action of formation, resulting in a good profile modification being achieved only in the near-wellbore zone. Alkali can form surfactants with the acidic components of crude oil, so it can emulsify the crude oil in situ to form an O/W emulsion and be produced with subsequent fluid injection . However, the absorption of alkali is serious and only the oil near a wellbore can be used .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the foam has the disadvantage of de-foaming in contact with oil, so the EOR is poor. , A polymer is used to increase the viscosity of the injected fluid and reduce the mobility ratio of injected fluid to crude oil to increase the swept area . But a long polymer chain would be severely fractured under the shearing action of formation, resulting in a good profile modification being achieved only in the near-wellbore zone. Alkali can form surfactants with the acidic components of crude oil, so it can emulsify the crude oil in situ to form an O/W emulsion and be produced with subsequent fluid injection . However, the absorption of alkali is serious and only the oil near a wellbore can be used .…”
Section: Introductionmentioning
confidence: 99%
“…20−22 Alkali can form surfactants with the acidic components of crude oil, so it can emulsify the crude oil in situ to form an O/W emulsion and be produced with subsequent fluid injection. 23 However, the absorption of alkali is serious and only the oil near a wellbore can be used. 24 Adding a small amount of emulsification flooding agent to water can provide a better EOR effect by using the adsorption characteristics of surfactants on an oil−water interface to emulsify the oil into the O/W emulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Maaref et al 27 found that at a higher viscosity ratio, the oil recovery is significantly high due to the viscous force enforced by the displacing phase. A few experimental studies by Heshmati et al 29 and Sharma et al 2 show that an increment in the displacing phase viscosity and flow rate applies a viscous force on the residual nonwetting phase. The viscous force results in a momentum transfer to the trapped phase, resulting in its being mobilized.…”
Section: Introductionmentioning
confidence: 99%
“…Heat and mass transfer processes in several applications such as electronics cooling, process intensification, microreactors in the manufacturing of pharmaceutical and fine chemicals, and enhanced oil recovery , involve complex gas–liquid flows in small diameter channels. In recent decades, the miniaturization of equipment has shown great applicability in terms of yield, design, handling, and safety.…”
Section: Introductionmentioning
confidence: 99%